2003
DOI: 10.1242/dev.00443
|View full text |Cite
|
Sign up to set email alerts
|

Notch activates sonic hedgehog and both are involved in the specification of dorsal midline cell-fates inXenopus

Abstract: We analysed the role of Notch signalling during the specification of the dorsal midline in Xenopus embryos. By activating or blocking the pathway we found that Notch expands the floor plate domain of sonic hedgehog and pintallavis and represses the notochordal markers chordin and brachyury, with a concomitant reduction of the notochord size. We propose that within a population of the early organiser with equivalent potential to develop either as notochord or floor plate, Notch activation favours floor plate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 89 publications
10
55
4
Order By: Relevance
“…There is strong evidence for a conserved role of Notch signaling in regulating hypochord allocation during gastrulation, but the signals regulating medial floor plate allocation are less clear (Appel et al, 1999;Latimer and Appel, 2006;Latimer et al, 2002;Peyrot et al, 2011). Speciesspecific roles for Notch and Midkine signaling have been identified, but a conserved pathway regulating this process across all species has yet to be identified (Gray and Dale, 2010;Lopez et al, 2003Lopez et al, , 2005Peyrot et al, 2011;Schafer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence for a conserved role of Notch signaling in regulating hypochord allocation during gastrulation, but the signals regulating medial floor plate allocation are less clear (Appel et al, 1999;Latimer and Appel, 2006;Latimer et al, 2002;Peyrot et al, 2011). Speciesspecific roles for Notch and Midkine signaling have been identified, but a conserved pathway regulating this process across all species has yet to be identified (Gray and Dale, 2010;Lopez et al, 2003Lopez et al, , 2005Peyrot et al, 2011;Schafer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the activation of Notch signaling by NICD decreases notochordal markers, such as Xbrachyury and chordin expression, in the dorsal midline during the Xenopus neurula stage (Lopez et al, 2003). Other studies indicate that Notch signaling is involved in the midline structure in zebrafish (Appel et al, 1999;Latimer et al, 2002).…”
Section: Regulation Of Xbrachyury By Xsu(h)2mentioning
confidence: 95%
“…Xotch is expressed ubiquitously at the early gastrula stage and is required for muscle formation (Coffman'et al, 1993). Notch signaling is involved in notochord patterning in the midline and L-R patterning in the lateral plate mesoderm (Latimer et al, 2002;Lopez et al, 2003Lopez et al, , 2005Raya et al, 2004); however, there is little information about the function of Notch signaling in germ layer formation during earliest embryogenesis. These results suggest that Notch signaling plays an active role in the cell fate decision in gastrula embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the choice of Hensen's node zone c cells to enter either the floor plate or the notochord differentiation pathway results from intrinsic cell fate decision and/or from extrinsic signals cannot be deduced from the previous data. However, recent results in several animal models are in favor of a balance between notochord and floor plate cells by cell fate decision at the level of the organizer (Appel et al, 1999;Lopez et al, 2003;Przemeck et al, 2003). Notch-Delta signaling is a good candidate for controlling this process.…”
Section: Hensen's Node Cell Fate and Differentiationmentioning
confidence: 99%
“…It has been shown that dlA mutants have a reduced number of floor plate cells and an excess of notochord cells, whereas embryos that over-express dlA have a reduced number of trunk notochord cells and an excess of floor plate cells. More recently, the role of Notch signaling was analyzed during specification of the dorsal midline in Xenopus embryos (Lopez et al, 2003). By activating or blocking Notch signaling, the authors found that Notch expands the floor plate domain of Xenopus embryos by stimulating Shh and pintallavis (HNF3β) and represses the notochordal markers chordin and brachyury.…”
Section: Hensen's Node Cell Fate and Differentiationmentioning
confidence: 99%